TATA KELOLA DAN KEPATUHAN SYARIAH SEBAGAI INSTRUMEN PENCEGAHAN MISSION DRIFT PADA KOPERASI SYARIAH DI INDONESIA - Supar Supar; Arief Safari; Amie Amelia (Institut Agama Islam K.H. Sufyan Tsauri, 2025)
Sharia cooperatives, as an integral component of Islamic Non-Bank Financial Institutions (LKSNB), play a strategic role in strengthening the economic structure of Muslim communities through a financial distribution mechanism rooted in justice and the values of maqāṣid al-sharī‘ah. However, the development of several sharia cooperatives in Indonesia has shown indications of mission drift, which is a shift in orientation from socio-economic objectives towards a profit-dominated agenda, risking the obscuring of foundational Islamic economic values that prioritize collective welfare. This study aims to analyze the relationship between the implementation of good governance and sharia compliance with the tendency of mission drift within Indonesian sharia cooperatives. Employing a descriptive qualitative approach utilizing secondary data sourced from reports issued by the Financial Services Authority (OJK), the National Committee for Sharia Economics and Finance (KNEKS), as well as internationally reputable academic publications , the findings reveal that the implementation of transparency, accountability, and the effectiveness of sharia supervisory mechanisms still faces structural challenges. Sharia Supervisory Boards (DPS) have not fully exercised their active role in ensuring operational adherence to sharia principles, while external pressures to accelerate asset growth and liquidity often stimulate deviation from the social mission. Therefore, this study emphasizes the urgent need for an integrative model that harmonizes the sharia governance framework with the cooperative governance model, enabling sharia cooperatives to uphold maqāṣid al-sharī‘ah values while simultaneously achieving equitable and sustainable economic performance